Perawatan Bayi Sehari-Hari Dengan Terapi Koplementer Baby Spa di Desa Samatan Dusun Timur Kecamatan Proppo Kebupaten Pamekasan - Misnawati Misnawati; Sari Pratiwi Apidianti (Pusat Riset dan Inovasi Nasional, 2024)
Infancy is a golden period as well as a critical period of growth and development, called the golden age because infancy is very short and cannot be repeated. Children's health problems are one of the main problems in the health sector currently occurring in Indonesia. The level of children's health reflects the health level of the nation. Based on these problems, children's health problems are prioritized in nation development planning (Roesli, 2016). The method used in this counseling is a participatory approach, namely approaching local community leaders to obtain permission and support in mobilizing mothers with babies to undergo baby spa (baby massage)..